The Use Of Fermented Water Hyacinth Leaves Flour In Feed For Growth Of Nilem Fish (Osteochilus hasselti) - Mutya Syaraswati; Indra Suharman; Adelina Adelina (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Water hyacinth (Eichhornia crassipes) can be used as fish feed and has a fairly high protein content ranging from 9.8-12.0%. This study aims to determine the effect of using fermented water hyacinth (Eichhornia crassipes) leaf flour in feed on the growth and feed efficiency of nilem fish (Osteochilus hasseltii). This research was conducted for 56 days at the fish nutrition laboratory and the Fisheries and Marine Reservoir, University of Riau. This study used a completely randomized design (CRD) with 5 treatment levels and 3 replications. The test feed used in this study was artificial feed with the substitution of soybean flour by fermented water hyacinth leaf flour (TDEGF), with TDEGF percentages of 0%, 25%, 50%, 75% and 100%. The test feed was given 10% of the weight of the biomass per day with the frequency of feeding three times a day, namely at 08.00, 12.00, and 16.00 WIB. Nilem fish with initial weight ranging from 2,07 ± 0,06 /head and put in cages measuring 1x1x1 m3 with a stocking density of 25 fish/m3. The container used for feed digestibility parameters was an aquarium measuring 60x40x40 cm3 with a stocking density of 20 fish/m3. The feed used for feed digestibility and protein digestibility parameters was added with 0.5% Cr2O3 of the total feed. Feed is given at satiation with a frequency of 3 times a day. Fish feces were collected and dried are tested for Cr2O3 and protein content. The results showed that the best treatment is P4 (100% TDEGF) with feed digestibility 37.50%, protein digestibility 61.98%, feed efficiency 31.23%, protein retention 20.22% and specific growth rate 2.75% and Survival rate is 100%.